Epithelioid solitary fibrous tumors from CNS and soft tissues: an unusual morphologic variant - Lina Zhao; Jiajing Ma; Jiacai Ren; Jingping Yuan; Huihua He; Yabing Huang; Honglin Yan (BMC, 2024)
Abstract Background Solitary fibroous tumors (SFTs) are distinctive soft tissue tumors characterized by rearrangements of NAB2-STAT6 gene, which are associated with thin-walled, branching, "staghorn"-shaped vessels. SFTs are originally classified as a type of hemangiopericytoma (HPC). Classical SFTs are composed of spindle to ovoid cells arranged haphazardly or in fascicles. Rarely, SFTs exhibit unusual morphological variants such as fat formation, giant cells, dedifferentiation, or epithelioid variant. The epithelioid cell variant, which is composed almost entirely of epithelioid cells and arranged in solid or nest patterns, is extremely rare and frequently malignant. Case presentation In this study, we reported three cases of epithelioid SFTs (ESFTs) located in extrathoracic sites (right lateral ventricle, right lumbar, left pelvis). All the subjects in this study were elderly, with a predominance of female patients, accounting for two out of the three cases, and only one case involved a male patient. The tumor cells were entirely composed of epithelioid cells and exhibited positive for CD34 and STAT-6 markers. Ultimately, the majority of cases (two out of three) were diagnosed as malignant SFTs. Conclusion This study aims to enhance the awareness of ESFTs. In these cases, irrespective of the onset location, the arrangement patterns of tumor cells, such as papillary structures and the morphology of epithelial-like cells, conspicuously lack the hallmark histological characteristics of Solitary Fibrous Tumors (SFTs). Consequently, it requires differential diagnosis from a plethora of malignant neoplasms. Moreover, the elevated malignancy level of this cohort of cases poses substantial diagnostic challenges to pathologists, compounding the complexity of accurate interpretation.